ADOPTIONOFHEALTHINSURANCESCHEMEANDHEALTHSEEKINGBEHAVIOURAMOGEMPLOYEESOFPRIVATEORGANISATIONS IN ENUGU STATE, NIGERIA (2023)
The Health Insurance Scheme (HIS), a means of financing medical care among employees globally, is designed to subsidise medical costs. In Nigeria, HIS is inadequately implemented and this affects access to healthcare among employees, particularly in the private sector. Existing studies have mainly focused on biomedical aspects of HIS in the public sector with scant attention given to the social factors associated with its utilisation among employees of private organisations, including Enugu State, where the scheme has officially been adopted by private sector organisations. This study, therefore, examined the extent to which HIS is utilised; influence of its adoption on health-seeking behaviour; treatment pathways of enrollees; gender differentials in its utilisation; and the challenges reported by private sector employers that have enlisted in the scheme in Enugu State. The Structural Functionalist Theory and Health Belief Model served as framework, while the cross-sectional survey design was employed. The purposive sampling technique was used to select one organisation from each of the manufacturing and service industries that have adopted HIS. A sample of 457 respondents were drawn using Yamane’s formula. Simple random sampling was used to proportionately administer semi-structured questionnaire to employees in manufacturing (369) and service (88) industries. Twenty-four in-depth interviews were conducted with employees in manufacturing (14) and service (10) industries. Sixteen key informant interviews were conducted with management staff of manufacturing (5) and service (3) industries. Four healthcare providers from National Health Insurance Agency (NHIA) accredited hospitals, two managers of health maintenance organisations, and two NHIA executive officers. The quantitative data were analysed using descriptive statistics, Logistic regression and T-test at p≤0.05, while the qualitative data were content-analysed. The respondents’ age was 38±2.4 years; 77.4% had tertiary education and 70.8% were married. Forty-six percent partially utilised and 32.0% adequately utilised HIS. The extent to which HIS was adequately utilised was significantly associated with respondents’ aged ≥50 years (OR=4.87), tertiary education (OR=3.53) and those who were married (OR=2.57). Influence of HIS on health-seeking behaviour was significantly associated with senior staff (OR=1.57) and 100, 000 (OR=4.04) as monthly income. The treatment pathways for employees started with visit to HIS hospitals (61.2%), home therapy (23.2%), visit to hospitals without HIS (12.5%), faith/religious centres (2.9%) and traditional medical centre (0.2%). Some of those who did not visit HIS accredited hospitals at the onset of their ill-health resorted to visiting HIS accredited hospitals when their conditiondeteriorated.Femaleemployees(52.6%)were more likely to seek healthcare through HIS than their male counterparts (47.4%) after enrolling in HIS plan. Private sector employers’ challenges in the adoption of HIS included payment of premium, abuse oftheschemebysomeemployees,complexbureaucratic structure of the scheme and employees' inability to access certain treatments due to their organisations’ chosen HIS plan.Socio-organisational and individual factors influenced the adoption of health insurance scheme and the health seeking-behaviour of private sector employees in Enugu State, Nigeria. Health maintenance officials, Healthcare providers and other stakeholders should therefore increase awareness about the benefits of utilising health insurance scheme by private sector employees in order to reduce out-of-pocket health expenditure.